2005
DOI: 10.1038/labinvest.3700205
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of heme oxygenase-1 in the progression of rat adjuvant arthritis

Abstract: Rat adjuvant arthritis is an experimental model widely used to evaluate etiopathogenetic mechanisms in chronic inflammation. We have examined the participation of heme oxygenase-1 (HO-1) in this experimental arthritis. In this study, an increased nitric oxide (NO) production in the paw preceded the upregulation of HO-1, whereas selective inhibition of inducible NO synthase (iNOS) after the onset of arthritis decreased HO-1 expression, suggesting that the induction of this enzyme may depend on NO produced by iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 59 publications
3
32
1
Order By: Relevance
“…SnPP also inhibited PGE 2 levels in inflamed tissues without modifying the expression of COX-2. These results suggest an inhibitory effect of SnPP on COX-2 activity, which is consistent with our findings in the rat adjuvant arthritis model (44).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SnPP also inhibited PGE 2 levels in inflamed tissues without modifying the expression of COX-2. These results suggest an inhibitory effect of SnPP on COX-2 activity, which is consistent with our findings in the rat adjuvant arthritis model (44).…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that HO-1 deficiency in mice results in a chronic inflammatory state (48). It is interesting to note that we have recently observed a therapeutic effect of HO-1 inhibition in rat adjuvant arthritis (44). Our data suggest that although HO-1 overexpression exerts some antiinflammatory effects in this murine model of chronic inflammation, it is unable to effectively control the progression of disease and prevent cartilage damage.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, very little HO-1 was detected in noninflammatory synovial tissues. HO-1 expression was also up-regulated in joint lesions in a model of rat adjuvant arthritis (27).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, a recent study revealed a pathologic role of HO-1 in the progression of adjuvant arthritis in a rat model (27), in that HO-1 expression was up-regulated in the joint lesions and that treatment with an HO inhibitor, tin protoporphyrin IX, suppressed leukocyte infiltration, hyperplastic synovitis, erosion of articular cartilage and osteolysis, and the production of inflammatory mediators. In that experimental rat model, HO-1 induced vascular endothelial growth factor (VEGF), which is involved in angiogenesis in inflammatory lesions in the joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation